Оцінка економічних збитків при виході з ладу електричного обладнання - Яковлєв, Анатолій Іванович; Корнус, Валерія Вадимівна (НТУ "ХПІ", 2015)
Проведено аналіз методичних положень визначення ефективності підвищення надійності електротехнічних виробів, які працюють в системі управління промисловими агрегатами промислових підприємств. Запропоновані засоби визначення величини відповідних збитків, наведені необхідні формули для проведення чисельних розрахунків величини збитків. Розроблено їх склад і структури. В тому числі для поточних і одночасних витрат. Такі розрахунки аргументуються на основі правила тотожності по варіантам.

The analysis of methodical positions determine the effectiveness of increasing the reliability of electrical products that function in the management of industrial units of the industrial enterprises . The methods of setting the value corresponding to its damage , given the necessary formulas for numerical calculations of damages. They developed their composition and structure, including current and non-recurring costs. Similar calculations are argued on the basis of the rules on identity options o for option, in which there is a certain decrease in output in case of failure of means of work, corresponding to estimates of the added value of the corresponding current and non-recurring costs for the alignment options to the level, which provides job. Accordingly, improving the reliability of the analyzed technology reduces simple process equipment, material damage in case of failure of electrical automation equipment, as well as the unnecessary loss of material, labor and financial resources. Reserves are determined to increase the reliability of the analyzed equipment.
Assessment of the economic damage caused by the failure of the electrical equipment
Keywords: інновації; вироби електротехнічні; обладнання технологічне; надійність; innovation; electrical products; manufacturing equipment